Dark souls : design works - Hayashi, M. Kirie (Richmond Hill, Ontario, Canada : UDON Entertainment Corp., 2013)
Showcasing the grim and chilling artwork behind the fan-favorite Dark Souls game, this hardcover collection features key visuals, concept art, character and monster designs, rough sketches, and an exclusive interview with the game's creators.
"First published in Japan in 2012 by ENTERBRAIN, INC., Tokyo"--Page [127].
Keywords: Computer adventure games -- Design